Analisis Tingkat Kemampuan Berpikir Kritis Mahasiswa pada Mata Kuliah Graf Materi Pewarnaan Simpul - Bettri Yustinaningrum; Ema Butsi Prihastari (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2023)
The top three levels in Bloom's taxonomy of learning objectives, which includes analysis, synthesis, and evaluation, are critical thinking skills. Critical thinking abilities among students range widely. Based on aspects of critical thinking and universal intellectual standards, this research seeks to investigate the level of critical thinking competencies of tadris mathematics students in the topic of node coloring graph material. Descriptive analysis is the method of research used in this qualitative research technique. 14 fourth-semester students served as the research subjects for this study, which was carried out at the Mathematics Tadris Study Program at Institut Agama Islam Negeri (IAIN) Takengon. The tools employed include validation sheets, interview sheets, and critical thinking skills. Tests and interviews are used to acquire data. There are five stages in the critical thinking level (TBK). According to the study's findings, no pupils met the criteria for critical (TBK 3) and very critical performance (TBK 4). The subject level of students' critical thinking is based on critical thinking components, with 3 students (TBK 2) being quite critical, 10 students (TBK 1) being less critical, and 1 student (TBK 1) not being critical (TBK 0). This research demonstrates that students' critical thinking skills are still very low, hence enhancements to teaching strategies and learning activities are required.